Plasma microRNAs as Biomarkers for Predicting Radiotherapy Treatment-Induced Cardiotoxicity in Lung Cancer - Paulina Kazlauskaitė; Ieva Vaicekauskaitė; Jonas Venius; Rasa Sabaliauskaitė; Rita Steponavičienė (Life)
Background: Lung cancer is the second most common malignancy and stands as a leading cause of cancer-related deaths worldwide. Currently, one of the main treatment options for lung cancer is radiotherapy, but this treatment is associated with complications, such as an increased risk of cardiac-related morbidity and mortality. However, currently available methods for predicting radiation-induced heart disease (RIHD) remain suboptimal. Methods: In this pilot study, using the RT-qPCR method, we analyzed the expression levels of six miRNAs (miRNA-1-3p, miRNA-21-5p, miRNA-24-3p, miRNA-29a-3p, miRNA-34a-5p, and miRNA-222-3p). Results: Fourteen pairs of locally advanced non-small-cell lung cancer patients’ plasma samples, taken before and after radiotherapy, were examined. It was observed that miRNA-1-3p, miRNA-21-5p, miRNA-24-3p, miRNA-29a-3p, and miRNA-222-3p were downregulated, while miRNA-34a-5p was upregulated in lung cancer patients’ plasma after treatment. Additionally, after definitive radiotherapy, patients with an increased NT-proBNP value displayed a statistically significant difference in miRNA-222-3p levels compared to the normal range of this indicator. The panel of the combined four miRNAs for assessing the risk of cardiac comorbidities demonstrated an AUC of 0.79, sensitivity of 71.43%, and specificity of 100%, with further improved values upon integration with clinical biomarker NT-proBNP. Conclusions: This pilot study shows that the identification of changes in miRNA expression levels in lung cancer patients’ plasma before and after radiotherapy could be used for the early diagnosis of RIHD.